If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 13g + -13x = 0 Reorder the terms: 13g + 20x + -13x = 0 Combine like terms: 20x + -13x = 7x 13g + 7x = 0 Solving 13g + 7x = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-7x' to each side of the equation. 13g + 7x + -7x = 0 + -7x Combine like terms: 7x + -7x = 0 13g + 0 = 0 + -7x 13g = 0 + -7x Remove the zero: 13g = -7x Divide each side by '13'. g = -0.5384615385x Simplifying g = -0.5384615385x
| -6x-35=-8x+11 | | x-2=(-7) | | 5x-40=11+2x | | -122+6x=-5x+53 | | X+.15x= | | -6-35=-8+11 | | -51+5x=-7x+105 | | 13b=b+37 | | 9.6+x=12.5 | | -11.2t-5(-7.1t-18.19)=-2(-11.8t+8.04) | | 3(3x-5)=4x+25 | | -155-8x=11x+92 | | 2(a-3)=8 | | -2x-6=72 | | 3x-79=92+12x | | 5y-10=5y | | (56654.56)x+34.67=3.14 | | -0.2352941176= | | -3x+4=30 | | 4(-8.9g-11.24)=-19.2g-15.44 | | -59+7x=x+121 | | -134+2x=46+11x | | 8y+2x+8=0 | | 500-30=130+20 | | 12u+20=-4(-2u-18) | | 4-6=-10 | | x^2=36y^2+5 | | -5(-7p+18)=5p | | 4*a+3=5+a | | 26b=19 | | -2n-25=13 | | 3x-5(2x-3)=4 |